Unilateral pubic hair growth: a paracrine finding indicative of underlying leydig cell tumor in a prepubertal boy - Gabriel van de Walle; Luca A. Morgantini; Bronwyn G. Long; Nicoleta C. Arva; Cristiana Hentea; Claudia C. Boucher Berry; Amanda Osta; Emilie K. Johnson (Urology Case Reports, 2025)
Leydig cell tumors (LCTs) are rare in children and typically present with testicular masses and signs of early puberty. We report a case of a 6-year-old boy presenting solely with precocious pubic hair growth. Ultrasound revealed a small right testicular mass and elevated serum testosterone. Intra-operatively, hair growth was more prominent on the affected hemi-scrotum. Testis-sparing surgery confirmed a benign LCT with adjacent increased spermatogenesis. This is the first known report of ipsilateral pubic hair as a presenting sign of LCT. Localized androgen excess may be an early clinical indicator to guide timely diagnosis and treatment.